Поліхромії Угнівської церкви Різдва Богородиці у контексті формотворчих пошуків першої третини ХХ століття - Якимова, О. (Народознавчі зошити, 2014)
У статті проаналізовані стінописи церкви Різдва Богородиці у містечку Угневі. Розглядаються художні формотворчі засади Дам’яна Горняткевича на прикладі фігуративних та орнаментальних поліхромій храму. Простежено вияви пізньосецесійної художньої стилістики та так званого українського стилю. In the article have been analyzed wall paintings of the church of Holy Virgin’s Nativity in small, but strong with national spirit and cultural heritage borderland town of Uhniv. The formative artistic principles created by the artist Damian Hornyatkevych have been considered through the figurative and ornamental polychromatic paintings of the temple. Interrelations and connections between characteristic features of the late Art Nouveau styling (called «secession» in its Viennese and Western Ukrainian variants) and so-called Ukrainian style have been traced and presented. В статье проведен анализ росписей церкви Рождества Богородицы в небольшом, но сильном национальным духом и культурной традицией приграничном городке Угневе. Рассматриваются созданные художником Дамианом Горняткевичем художественные формообразующие основы фигуративных и орнаментальных полихромий храма,. Прослежены проявления позднесецессионной художественной стилистики и так называемого украинского стиля.